A Preliminary Study to Develop a Collaborative Tiered School-Based Physical Therapy Service Delivery Model: Results from an International Delphi Consultation (International Journal of Physiotherapy, 2022)
Background: Physical therapy (PT) is increasingly provided at schools to help students participate in educationalactivities. Recent rehabilitation models emphasized the benefits of using collaborative tiered services for serviceprovision, yet no model is available to guide how these services should be delivered. Therefore, this study aims to determine the core attributes and PT interventions of a collaborative tiered school-based PT model that could guide how PT services are delivered in schools worldwide.Methods: A modified Delphi method was used to identify the core attributes and the PT interventions that would be part of the model. An introductory webinar followed by three Delphi rounds with 24 international experts was conducted. Similar ideas generated in Round 1 were combined into statements; the statements reaching the predetermined consensus level in Rounds 2 or 3 were retained. Categories were created to present core attributes and Tiered interventions that were retained.Results: 41 core attributes were identified and grouped under seven categories. Tiered interventions were grouped under 15 categories which included 37 interventions for Tier 1, 24 interventions for Tier 2, and 60 interventions for Tier 3.Conclusion: The recommended core attributes and interventions will support the development of an international framework for school-based PT services, fostering health promotion for all children, and supporting those with disabilities.